The right to counsel in Iranian criminal justice system. - Rahmdel, Mansour; Rahmdel, Naser (Crime, Law & Social Change, 2013)
Criminal law deals with very important aspects of the life in the society. The subjects of the crime, health, reputation ... are so important that endangering them requires punishment and it is told that the society in order to protect the public order should punish the perpetrators. There is no doubt that the criminals should be punished. The punishment enacted by the legislator should be proportional. The more serious the crime, the more severe the punishment. But, it seems that in the process of criminal trial, the accused has rights too. It means that society has not an absolute authority in accusation and punishment and in addition to the proportionality and justification of punishment the trial should be fair. In other words, it is not possible to speak about justice any more if the criminal is punished proportionally and rightly but not fairly, i.e. without allowing him/her to present his/her case, defend him/herself and obtain legal aid or sufficient information. Iranian criminal law, like other criminal justice systems in respecting the rights of the accused, has provided the right to counsel. This value can be expressed in the concept of the rule of law, recognized in international documents. It seems that the standards of the criminal procedure are mostly determined and developed under the influence of this concept. The current paper considers different aspects of the right to counsel in Iran.